Another Commentary from Optina Pustyn on the Novel The Brothers Karamazov - Boris N. Tikhomirov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article is an attempt to comment on an “obscure” passage of the novel The Brothers Karamazov that the author maintains to be linked with the “cryptogrammatic level of the textual structure” of the novel (the term was borrowed from V.N. Toporov). The episode here analyzed should be related to the trip to Optina Pustyn Dostoevsky made in June 1878, little before the beginning of his work on The Brothers Karamazov, and the private conversation he had with the famous starets Ambrose. A key element for commentary turns out to be a note by A.G. Dostoevskaya about Dostoevsky’s visit at the Orthodox monastery, relatively newfound (2016) and introduced into the academic discourse by I. S. Andrianova. Notably, Anna Grigoryevna witnesses about starets Ambrose’s words, underlying the importance of rigorous sexual abstinence in the eve of Marian feast days. The article also provides with a clarification about this rule by contemporary theologian and priest father Georgy (Orekhanov).